High energy supercapattery with an ionic liquid solution of LiClO4 - Yu, Linpo; Chen, George Z. (Royal Society of Chemistry, 2016)
A supercapattery combining an ideally polarized capacitor-like electrode and a battery-like electrode is demonstrated theoretically and practically using an ionic liquid electrolyte containing 1-butyl-1-methylpyrrolidinium tri(pentafluoroethyl)trifluorophosphate (BMPyrrFAP), gamma-butyrolactone (γ-GBL) and LiClO4. The electrochemical deposition and dissolution of lithium metal on a platinum and glass carbon electrode were investigated in this ionic liquid solution. The CVs showed that the fresh electrochemically deposited lithium metal was stable in the electrolyte, which encouraged the investigation of this ionic liquid solution in a supercapattery with a lithium battery negative electrode. The active material counted specific energy of the supercapattery based on a lithium negative electrode and an activated carbon (Act-C) positive electrode could reach 230 W h kg−1 under a galvanostatic charge–discharge current density of 1 mA cm−2. The positive electrode material (Act-C) was also investigated by CV, AC impedance, SEM and BET. The non-uniform particle size and micropores dominated porous structure of the Act-C enabled its electric double layer capacitor (EDLC) behavior in the ionic liquid solution. The measured specific capacitance of the Act-C in this ionic liquid solution is higher than the same Act-C in aqueous solution, which indicates the Act-C can also perform well in the ionic liquid electrolyte.